1994
DOI: 10.1182/blood.v84.10.3385.3385
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of regulatory elements in the 5'-flanking region of the rat GPIIb gene by studies in a primary rat marrow culture system

Abstract: Glycoprotein (GP)IIb/IIIa, an integrin complex found on the surface of platelets, is a receptor for fibrinogen and other ligands, and is involved in platelet aggregation. Because GPIIb is specifically expressed in megakaryocytes, we have studied the 52-flanking region of the rat (r) GPIIb gene as a model of a megakaryocyte-specific gene. The studies presented here used a rat marrow expression system, which allows the study of primary cells undergoing terminal differentiation into megakaryocytes. The determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…A number of megakaryocyte‐specific regulatory regions have been studied recently, including the glycoprotein IIb promoter (Lemarchandel et al ., 1993; Block et al ., 1994) and enhancer (Prandini et al ., 1992), the thrombopoietin receptor promoter (Deveaux et al ., 1996) and enhancer (Mignotte et al ., 1996) and the GpIb α promoter (Hashimoto and Ware, 1995). All these contain binding sites for GATA‐1 and proteins of the Ets family, usually 15–35 bp apart (Lemarchandel, 1993), which are crucial for expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of megakaryocyte‐specific regulatory regions have been studied recently, including the glycoprotein IIb promoter (Lemarchandel et al ., 1993; Block et al ., 1994) and enhancer (Prandini et al ., 1992), the thrombopoietin receptor promoter (Deveaux et al ., 1996) and enhancer (Mignotte et al ., 1996) and the GpIb α promoter (Hashimoto and Ware, 1995). All these contain binding sites for GATA‐1 and proteins of the Ets family, usually 15–35 bp apart (Lemarchandel, 1993), which are crucial for expression.…”
Section: Discussionmentioning
confidence: 99%
“…A number of marker genes of the megakaryocytic lineage have been studied recently. These include the genes for glycoprotein IIb, thrombopoietin receptor ( MPL ), platelet factor 4, glycoproteins Ibα, V and IX and P‐selectin (Ravid et al ., 1991; Prandini et al ., 1992; Hickey and Roth, 1993; Lanza et al ., 1993; Lemarchandel et al ., 1993; Pan and McEver, 1993; Block et al ., 1994; Hashimoto and Ware, 1995; Deveaux et al ., 1996). The regulatory regions of these genes are characterized by the presence of closely spaced binding sites for GATA‐1 and proteins of the Ets family, but they do not contain NF‐E2 binding sites and their expression in the megakaryocytes of p45‐deficient mice is normal (Shivdasani et al ., 1995; Shivdasani, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…One of the first successful studies examining transgene expression within cultured megakaryocytes was initiated by Block et al . in 1994 with the demonstration of reporter assays using the GPIIb gene promoter following electroporation of plasmid cDNA constructs into rodent megakaryocytes [68]. The advent of a megakaryocyte growth factor, c‐mpl ligand [69,70], resulted in additional molecular‐genetic/functional studies that permitted production of a substantial quantity of cultured human megakaryocytes derived from bone marrow, cord blood and granulocyte‐colony stimulating factor‐mobilized peripheral blood cells (G‐PBC) [71–73].…”
Section: Can Bone Marrow Stem Cells Be Given Sufficient Genetic Informentioning
confidence: 99%
“…Following transduction of human CD34+ TG‐PBC with a MuLV retrovirus construct under control of an 889 nucleotide fragment of the human GPIIb promoter, we observed (i) lineage‐specific transgene expression of a reporter gene in megakaryocytes derived from cultured cells of normal individuals [76], and (ii) ex vivo correction of the GT phenotype following the targeted expression of the human GPIIIa subunit in megakaryocytes derived from cultured cells of patients with type I GT [79]. Nucleotide sequence analysis showed that the human GPIIb promoter has a high degree of homology with the rodent GPIIb promoter [68], and further studies demonstrated that the human promoter fragment could drive ‘species‐independent’ megakaryocyte‐specific gene expression in transgenic mice [60]. Likewise, methods are currently being developed for using a human GPIIb promoter‐controlled lentivirus vector for gene therapy in mice and dog models affected with platelet defects.…”
Section: Can the Newly Synthesized Receptor Be Maintained As A Platelmentioning
confidence: 99%
“…The results obtained to date by several groups [6, 19,20,24] indicate that proteins of the GATA and Ets families are necessary to activate megakaryocytic genes. However, other factors are certainly involved in the restriction of expression between erythroid and megakaryocytic cells; the negative activity binding on the GPIIb promoter ( [25] and G. Uzan, personal communication) and the factors that bind at -140 and +30 on the MPL promoter are good candidates for this function.…”
Section: Discussionmentioning
confidence: 99%